2022
DOI: 10.3390/v14071513
|View full text |Cite
|
Sign up to set email alerts
|

Avian Bornavirus Research—A Comprehensive Review

Abstract: Avian bornaviruses constitute a genetically diverse group of at least 15 viruses belonging to the genus Orthobornavirus within the family Bornaviridae. After the discovery of the first avian bornaviruses in diseased psittacines in 2008, further viruses have been detected in passerines and aquatic birds. Parrot bornaviruses (PaBVs) possess the highest veterinary relevance amongst the avian bornaviruses as the causative agents of proventricular dilatation disease (PDD). PDD is a chronic and often fatal disease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 242 publications
1
41
0
Order By: Relevance
“…This could explain the lack of neurological signs despite the morphological evidence of encephalitis, as well as the lack of neuronal necrosis. By contrast, the neuroinflammation caused by other orthobornaviruses, such as BoDV-1, variegated squirrel bornavirus 1 (VSBV-1), and parrot bornavirus-2 (PaBV-2), can result in disease development driven by T-cell-dominated immunopathogenesis, often resulting in histological evidence of neuronal degeneration [ 2 , 14 , 43 , 44 , 45 ]. In one genome-wide RNAseq study, the BoDV-1 infection of newborn rats led to neurological signs in the animal, and the transcriptomic analysis of their brains showed the upregulation of inflammatory cytokines [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain the lack of neurological signs despite the morphological evidence of encephalitis, as well as the lack of neuronal necrosis. By contrast, the neuroinflammation caused by other orthobornaviruses, such as BoDV-1, variegated squirrel bornavirus 1 (VSBV-1), and parrot bornavirus-2 (PaBV-2), can result in disease development driven by T-cell-dominated immunopathogenesis, often resulting in histological evidence of neuronal degeneration [ 2 , 14 , 43 , 44 , 45 ]. In one genome-wide RNAseq study, the BoDV-1 infection of newborn rats led to neurological signs in the animal, and the transcriptomic analysis of their brains showed the upregulation of inflammatory cytokines [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…ABBV-1 has a broad host range, and natural infection with this virus has been identified in ratites, raptors, and gulls, which are taxonomically distant from waterfowl species [ 11 , 12 , 13 ]. Given the circulation of bornaviruses in multiple avian species [ 14 ], it is possible that ABBV-1 could spill over and infect domestic poultry. Two recent studies from our group support this notion, as we have shown that ABBV-1 can infect and establish persistent infection in the nervous tissues of Muscovy ducks ( Cairina moschata ) and chickens ( Gallus gallus ), upon intracranial and intramuscular inoculation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the description of Borna disease virus 1 (BoDV-1) in horses causing neurologic disorders (Borna disease), further family members have been discovered in the last years including five virus species affecting a variety of birds. Currently a novel naming of the members of the virus family Bornaviridae following a uniform binomial Linnean format was introduced by the International Committee on Taxonomy of Viruses (ICTV) [ 1 , 2 ] and mentioned in the latest official update on bornaviruses [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, parrot bornaviruses were detected as the cause of a fatal disease known as Proventricular Dilatation Disease (PDD) in Psittaciformes [ 5 , 6 ]. Parrot bornavirus 2 (PaBV-2) and PaBV-4 belonging to the genus Orthobornavirus and the species Orthobornavirus alphapsittaciforme are the primary affectants resulting in PDD, causing predominantly nervous and gastrointestinal symptoms [ 4 ]. Besides the classical PDD, subclinically PaBV-infected carriers and various combinations of viral distribution, inflammatory lesions, and disease status have also been described [ 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, after the discovery of the first avian bornavirus in 2008 [ 78 , 79 ], a variety of bornaviruses have been detected in birds [ 80 ]. In particular, PaBV-4, which is the most dominant genotype causing neurological disorders and proventricular dilatation disease (PDD), has been detected in a broad range of captive psittacines worldwide [ 81 , 82 ], resulting in great economic damage to the bird breeding industry.…”
Section: Perspectivesmentioning
confidence: 99%